Russian space meets western business practices: Understanding the law in the petroleum sector in Russia - Goes, Sander (Nordlit, 2017)
<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-theme-font: minor-bidi;" lang="EN-US">This article discusses the relationship between the private international oil company (IOC) Royal Dutch Shell and Russia as an oil producing and oil exporting state during<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-theme-font: minor-bidi;" lang="EN-GB"> a period when oil prices were moving towards unforeseen heights (2005-2007)<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-theme-font: minor-bidi;" lang="EN-US">. By examining this dynamic relationship, this study aims to contribute to an understanding of Russia’s discursive and culturally produced history. <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: Arial; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The history of a state-oil company interaction has shown that the use of legal instruments is a good indicator to determine the nature of the relationship between oil-producing states and IOCs – a relationship that<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: NL; mso-bidi-language: AR-SA; mso-bidi-theme-font: minor-bidi;" lang="EN-GB"> often has been characterized by periods of cooperation or conflict.<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-theme-font: minor-bidi;" lang="EN-US">At the centre of inquiry is how the oil major understands the law in Russia, and in particular the enforcement of the country’s formal written rules during legal conflicts over the development of the Sakhalin-II oil and gas fields (in which Shell until December 2006 controlled a majority stake). After identifying the violations of formal laws, I conclude that Shell understands that the formal rules of the game are subordinate to the unwritten laws of energy politics and in particular the informal demands of contemporary Russian society<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: NO-BOK; mso-bidi-language: AR-SA; mso-bidi-theme-font: minor-bidi;" lang="EN-GB">. The article also illustrates that oil-producing states have the upper hand in conflicts over the development of oil and gas resources.